Boundary Value Problems for Second-Order Finite Difference Equations and Systems - Henderson, Johnny; Luca, Rodica (Boston: DeGruyter, 2023)
Second-order finite difference equations with multi-point boundary conditions -- Systems of second-order finite difference equations with uncoupled multi-point boundary conditions -- Systems of second-order finite difference equations with nonnegative nonlinearities, coupled multi-point boundary conditions, and positive parameters -- Systems of second-order finite difference equations with nonnegative nonlinearities, coupled multi-point boundary conditions, without parameters -- Systems of second-order finite difference equations with sign-changing nonlinearities and coupled multi-point boundary conditions -- Nonlinear fractional difference eqautions with nonlocal boundary conditions
Keywords: Difference equations; Boundary value problems; Boundary value problems; Difference equations